PROBLEMATIKA PEMBELAJARAN DARING (Kesulitan Yang Dihadapi Guru Dan Siswa SMP Swasta Nur Ihsan) - Abdul Muthalib, Azhar Lubis, Indah permata Sari Sinaga, Mahrani (Yayasan Pendidikan Islam dan Multikultural, 2022)
Abstract: This study aims to analyze the difficulties facing teachers and private junior high school students Nur Ihsan, with two focus research studies that are problematic use of online learning media for teachers and students, printing a sanctions of online learning material for teachers and students. This research is implemented in private junior high school nur Ihsan on Febuari-October 2021. This research uses a qualitative method based on case studies. Data collection using observation, interview and documentation techniques. Then in the analysis with the data reduction stages, data sanctions, and concludes. The results showed that (1) Problematic Media's use of online learning for teachers and students at private junior high school Nur Ihsan in the COVID-19 period: The teacher is only bias using the WhatsApp app for teaching and learning processes, not utilizing other learning applications, not all students have a mobile phone, unstable network due to the conditions of residence from teachers or students who have unexed internet connection and purchase of expensive internet quotas. (2) Problematics in the Energy Learning Materials for Master and Private SMP Students Nur Ihsan in the Cove